1 g Model Test on the Use of Isolation Piles for Tunnel Protection Adjacent to Soft Soil Excavation. (July 2022) - Liu, Kui; Xu, Xiao Bing; Hu, Qi; Zeng, Li Bin; Wang, Jin Chang
Abstract: As the rapid development of urbanisation, the available land resource is getting gradually limited. In correspondence, underground constructions become popular and the influence of soil excavation adjacent to shield tunnel has become a great concern. However, the role of isolation piles for tunnel protection in soft soil conditions has not been well understood, owing to a lack of practical data. In this paper, an 1 g model test, with three experimental patterns, that is, C1 (no isolation piles), C2 (non-buried isolation piles) and C3 (buried isolation piles), was designed based on a prototype work in Zhejiang Province (China). A similarity concept was considered for the rescaling of the model test. The displacements and bending moments of the retaining wall, isolation piles and shield tunnel, were monitored and assessed, respectively. The results showed a barrier role of isolation piles which could restrict the displacements and bending moments of the retaining wall, particularly C2 with non-buried isolation piles which was shown to be more effective than the buried isolation piles in C3. The buried isolation piles played a better barrier role than that of the non-buried isolation piles in terms of restricting the tunnel displacements. The circumferential bending moment of the tunnel could not be restricted by using isolation piles under the investigated scenarios. The working mechanism of isolation piles was evaluated, which suggested the importance of a proper designed locations of foundation pit and isolation piles. Regardless of the limitations, the findings obtained from this study would be useful for future applications of isolation piles in tunnel protection with adjacent soil excavation.